(untitled) (Global Journal of Human-Social Science, 2013)
In today’s world where the information changes and improves at a great speed, societies need individuals who can access more information, adapt themselves with this new kind of information and keep up with the pace of changing world. In a sense, individuals need to renew themselves and have lifelong learning skills beyond basic skills. In line with technological developments, what the limits of formal education institutions are and whether they meet the needs of the society have been examined. The discussions about individuals’ reflecting their education and learning processes into every aspect of their lives, acquiring basic skills regardless of age range and then providing education opportunities at advanced levels have brought forward the practices of open and distance education. Open and distance education opportunities enable the individuals to improve their information, abilities and qualifications and to provide them with new opportunities within the frame of life-long learning process through learning activities at every moment of life and prepare them for new experiences. One of the opportunities of open education is "Open Elementary School", which aims to develop and strengthen the society by providing the elementary education to the individuals who are over compulsory education age and have not completed their primary education yet. This can be done through advanced communication tools and technologies in line with the general purpose and basic principles of Turkish National Education by Ministry of Education. Open Elementary School also aims to provide opportunities to the students who could not have enough education opportunities to eliminate their deficiencies, to create opportunities to prepare them for the next stage and make them to be able to develop behaviors that will guide them to a profession through contemporary information technologies. In this study, the reasons of their enrollment in Open Elementary School and the views of the students on Open Elementary School Practices have been analyzed descriptively. The data of the study was collected from 207 voluntary students who enrolled in Open Elementary School in Ankara. In the study, "Open Elementary School New registry/Reregistration Evaluation Form developed by the researchers was used. Face-to-face interviews with the students enrolled were conducted and the forms were completed during those interviews.